2016
DOI: 10.1002/2015wr018023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a semimechanistic episodic Langevin model for bed load transport: Emergence of normal and anomalous advection and diffusion regimes

Abstract: Bed load transport is a highly stochastic, multiscale process, where particle advection and diffusion regimes are governed by the dynamics of each sediment grain during its motion and resting states. Having a quantitative understanding of the macroscale behavior emerging from the microscale interactions is important for proper model selection in the absence of individual grain-scale observations. Here we develop a semimechanistic sediment transport model based on individual particle dynamics, which incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 61 publications
2
55
1
Order By: Relevance
“…Making an analogy with Brownian motion in a potential well, Ancey and Heyman [] assumed that F behaves like white noise and 〈 F 〉 relaxes to its steady state value over a certain characteristic time, and thereby they deduced that P ( u p ) was a truncated Gaussian distribution, a form supported by experimental evidence [ Martin et al , ]. Assuming that 〈 F 〉 was constant and particles move sporadically, Fan et al [] found that particles may exhibit subdiffusive, normal, or superdiffusive behavior depending on the resting time. While particle diffusion and more specifically the determination of particle diffusivity have been addressed experimentally [ Heyman et al , ; Seizilles et al , ], there is scarce information on how D u varies with the flow conditions.…”
Section: Theoretical Backgroundcontrasting
confidence: 99%
See 1 more Smart Citation
“…Making an analogy with Brownian motion in a potential well, Ancey and Heyman [] assumed that F behaves like white noise and 〈 F 〉 relaxes to its steady state value over a certain characteristic time, and thereby they deduced that P ( u p ) was a truncated Gaussian distribution, a form supported by experimental evidence [ Martin et al , ]. Assuming that 〈 F 〉 was constant and particles move sporadically, Fan et al [] found that particles may exhibit subdiffusive, normal, or superdiffusive behavior depending on the resting time. While particle diffusion and more specifically the determination of particle diffusivity have been addressed experimentally [ Heyman et al , ; Seizilles et al , ], there is scarce information on how D u varies with the flow conditions.…”
Section: Theoretical Backgroundcontrasting
confidence: 99%
“…The first family follows the Lagrangian framework, in which particles are tracked individually. To deduce the bulk properties, such as particle flux and activity (i.e., the number of moving particles per unit streambed area), recent studies have focused on the statistical properties of particle trajectories in their random walks [Ganti et al, 2010;Furbish et al, 2012bFurbish et al, , 2012cArmanini et al, 2014;Pelosi et al, 2016;Fan et al, 2016]. An alternative is the Eulerian framework, which derives the bulk properties by averaging particle behavior over a control volume [Ancey et al, 2008;Ancey and Heyman, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The approach taken in this section is an alternative way to account for the intermittence of the bed load process. It is closely related to an entrainment‐disentrainment form of the Exner equation (e.g., Ancey, ; Ancey & Heyman, ; Ballio et al, ; Charru et al, ; Lajeunesse et al, ), as well as to modeling the particle trajectories as random walks (e.g., Fan et al, ; Lisle et al, ). From a phenomenological point of view, the persistence of motion is also obviously related to the characteristics of particle hops (e.g., Campagnol et al, ; Fathel et al, ; Hu & Hui, ; Lee et al, ; Ramesh et al, ).…”
Section: Persistence Of Motionmentioning
confidence: 99%
“…Bedload is a common mechanism of sediment transport for sand particles in natural flow, characterized by cyclic sequences of particles moving and resting on the sediment bed (e.g., Fan et al, , ; Furbish et al, ; González et al, ; Lajeunesse et al, ; Roseberry et al, ). The physical mechanisms governing bedload transport are highly complex due to (i) the turbulent fluctuations of the flow and (ii) random interactions of grains with each other and with the bed, over a wide range of bed topography and corresponding flow scales, from the grain size to the reach (e.g., Bagnold, ; Church, ; Furbish et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential source of variability is the effect of sediment‐mixture heterogeneity (Houssais & Lajeunesse, ), which could be related to the different waiting‐time distributions proposed in the literature. All of these issues are important for the physical understanding of sediment‐transport mechanisms, for the correct prediction of particle trajectories (microscale), and for the advection and diffusion properties of the particle ensemble (macroscale), as discussed above (Han & He, , Nikora et al, ; Fan et al, , Weeks et al, , Schumer et al, b, and Fan et al, ).…”
Section: Introductionmentioning
confidence: 99%